How Do the Teachers Define Social Studies Course? - TOPÇU, Ersin (Asian Educational Journal Publishing Group, 2017)
In this research, the aim is to determine what the social studies teachers think about the interdisciplinary structure of the social studies course and the educational situation. Likert type questionnaire and semi-structured interview form were used as data collection tools. The questionnaire was applied to 150 teachers working in 58 secondary schools in 27 provinces in Turkey. The form was applied to 10 teachers from the same group. The data was interpreted by descriptive analysis. When the results were evaluated, it was determined that the teachers had some problems arising from the multidisciplinary nature of the course and thought that the interdisciplinary connections between different disciplines could not be done well. There is no consensus among the teachers about the nature of the social studies course, and some teachers especially think that history and geography should be given as separate courses.
Keywords: 4. Education; 10. No inequality